Faktor-Faktor yang Mempengaruhi Pengambilan Kredit di LPD Desa Adat Pujungan, Kecamatan Pupuan, Kabupaten Tabanan - ASTRAWAN, I KADEK; SUAMBA, I KETUT; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
The Factors That Affect Credit Decision Making In LPD Of Pujungan Village, Pupuan Sub-District, Tabanan Regency One of the economic development in Indonesia is supported by the Rural Credit Institution (LPD) of Pujungan Village, Pupuan Sub-District, Tabanan Regency. The efforts to maintain and increase its continuity, LPD also needs to look at the factors that affect the debtor in making credit decisions. The purpose of this research is to determine the factors that influence the debtor’s decision in taking credit and the suitability of credit usage by the debtor. The sampling technique in this research was carried out by random sampling. The analysis technique used is multiple linier regression analysis. The results showed that interest rates, services, and procedures for lending had a positive and significant effect on debtor decisions in taking credit, and the suitability of use tends to productive loans.